Immune and immune-histochemical response for bivalent attenuated vaccines against Newcastle and infectious bronchitis diseases in broilers - Mohammad S. Al-Zebary; Fanar A. Isihak; Waseem H. Al-Jameel (Iraqi Journal of Veterinary Sciences)
This study intended to research the immunological and immune-histochemical outcomes of 6 bivalent live vaccines against NDV and IBV. Two hundred ten, 1-day old chicks divided equally into 7 groups. The chicks of group 1 received (the Nobilis MSD® vaccine). G2 vaccinated with (Hipraviar® vaccine). G3 performed with (Vaxxinova® vaccine). G4 given (Komipharm® vaccine). G5 vaccinated with (KAVAC® vaccine). G6 vaccinated by (Dagluban® vaccine). Group 7 (negative control). The groups G1 to G6 were vaccinated by the ocular route at 1 and 14 days of age with the abovementioned vaccines. Serum samples were collected for ELISA and HI tests, while tracheal tissue was collected for histochemical and immunohistochemical Staining. The high titer of Abs against NDV was observed mainly in G1 on days 21, 28, and 35 when compared to other groups of different ages. IBV ELISA findings showed that G1 had a greater Abs at day 21 than G4 and G6, whereas G2 explained a significantly higher titer of Abs at day 28 than other groups. The HI results indicate a bimodal and fluctuating titer of Abs. Assessment of tracheal mucin pictures found that MUC5AC and MUC5B immunostaining were significant in group 5 after 7 and 21 days. MUC5AC immunostaining was high in more than half of the epithelial cells in group 2. In conclusion, some of the tested vaccines provided a sufficient amount of Abs against NDV and IBV diseases. Mucin illustrated high to moderate expression in the epithelial surface and goblet cells associated with groups of experiments.